Governance challenges of flood-prone delta cities: Integrating flood risk management and climate change in spatial planning. (May 2017) - Francesch-Huidobro, Maria; Dabrowski, Marcin; Tai, Yuting; Chan, Faith; Stead, Dominic
Highlights: Delta cities are increasingly exposed to the risks of climate change. Dominant institutional characteristics associated with spatial development visions, strategies, plans and programmes in the three cities are examined. The spatial development, flood risk management and governance dynamics shaping climate adaptation decisions/responses are explored. Dominant institutional characteristics critically affect the steering capacity of institutions to address climate-related risks. Abstract: Delta cities are increasingly exposed to the risks of climate change, particularly to flooding. As a consequence, a variety of new spatial development visions, strategies, plans and programmes are being developed by city governments in delta regions to address these risks and challenges. Based on a general conceptual framework, this paper examines the nature of visions, strategies, plans and programmes in the delta cities of Hong Kong, Guangzhou and Rotterdam which are highly exposed to flooding and connected through a network of epistemic communities. The paper follows two main lines of inquiry. First, it examines the terms, concepts, and dominant institutional characteristics associated with the development of these visions, strategies, plans and programmes as a way of constructing a conceptual framework for understanding and explaining their connectivity. Second, it explores how and why cities' spatial plans and governance dynamics are shaping climate adaptation responses. The systematic development of conceptual frameworks and in-depth analyses of varied, representative case studies is needed as their findings have important implications for vulnerability and adaptation to climate change in terms of policy options and cities as the optimal level for adaptation. The paper finds that dominant institutional characteristics critically affect the steering capacity of organisations/agencies (including their coordination capacity) to address climate-related risks. The findings have important implications for vulnerability and adaptation to climate change in cities, in general and delta cities, in particular.